PLANNING ANALYSIS OF KALEDUPA PORT WHARF BY USING SAP2000 SOFTWARE - I Gusti Ngurah Bagus H. K.; Suwandi Saputro (International Journal on Livable Space, 2022)
Kaledupa Port is a public port that serves a limited number of domestic sea transportation activities. With the growth of the tourism sector in Wakatobi Regency, especially at Kaledupa Island, the operational intensity of the Kaledupa port has also continued to increase. One of the efforts that can be made in the development of Kaledupa Port is to analyze the planning of the Kaledupa Port wharf for quality improvement and evaluation at the Kaledupa Port. This study aims to find out what kind of loads work on the wharf which can then be modeled for wharf planning in the SAP2000 software. Based on the planning analysis, the Kaledupa port wharf is planned to have a length of 82 m and a width of 10 m with a general cargo ship with a maximum weight of 1,000 DWT. The results of the wharf modeling in the SAP2000 software with steel piles with a diameter of 508 mm and a thickness of 14 mm with a carrying capacity is 86.31 tons and based on the carrying capacity of the soil at location BH-02 the soil carrying capacity is 158.88 tons at a depth of 23 m with hard soil or coral conditions.